Technical note: A model of chemical transport in a wellbore–aquifer system - Y. Gan; Y. Gan; Q. Wang; Q. Wang (Hydrology and Earth System Sciences, 2024)
Wellbore is proven to be the only effective way of delivering chemicals to a target aquifer during a tracer test or aquifer remediation. The volume of original water in the operational well is a critical parameter affecting the concentration of injected tracers or chemicals in the wellbore in the early stages. We found that the calculation of the wellbore water volume by previous numerical methods was correct when the wellbore penetrates an unconfined aquifer but incorrect when the wellbore penetrates a confined aquifer, further resulting in errors in describing the solute transport of injected chemicals in confined aquifers, such as MODFLOW/MT3DMS or FEFFLOW. Such errors caused by MODFLOW/MT3DMS and FEFFLOW increased with increasing wellbore water volume. This was because the groundwater in both the wellbore and aquifer was assumed to be confined where the water level was higher than the aquifer's top elevation and the groundwater thickness was assumed to be equal to the aquifer thickness. Actually, when the wellbore penetrated a confined aquifer, the groundwater was only confined in the aquifer, while it was unconfined in the wellbore. In this study, the solute transport model is revised based on the mass balance in a well–aquifer system, with special attention given to the wellbore water volume. The accuracy of the new model was tested against benchmark analytical solutions. The revised model could increase the accuracy of reactive transport modeling in aquifer remediation through the wellbore.